Dampak Pendayagunaan Infaq Produktif Terhadap Peningkatan Pendapatan Pada Mustahiq YDSF (Yayasan Dana Sosial Al-Falah) di Kediri - Chandra Ari Haryanto; Nisful Laila (Universitas Airlangga, 2014)
The impact of infaq productive utilization of the increased income on mustahiq YDSF (Foundation of Social Funds Al-Falah) in Kediri. The goal of this research is to know the impact of utilization of infaq productive done by mustahiq to increase revenues.The research method used is a qualitative approach, strategy case studies andanalysis techniques, descriptive data collection is done through interviews and observations of the informants. Informants were participants KUM (Independent Business Group) in Kediri composed of 8 people who have attended this program and get help infaq in the from the board LAZ YDSF (the foundation of social funds al-falah) through KUM.Result from this study that the productive utilization of infaq by mustahiq through KUM (Independent business group) in the form of venture capital has an impact on income growth mustahiq. Can be seen that the eight mustahiq interviewed seven mustahiq who experienced improvement, where as only one mustahiq whose income is not increasing. REFERENCES Al Qur’an dan terjemahannya. Departemen Agama Republik Indonesia.Alwi, Hasan dkk. 2002. Kamus Besar Bahasa Indonesia Edisi Ketiga. Balai Pustaka: Jakarta.Antonio, M. Syafi’i. 1999. Bank Syaria: Wacana Ulama dan Cendekiawan. Jakarta:Tazkia Institute.Hasan, M. Ali. 2008. Zakat dan Infaq: Salah Satu Solusi Mengatasi Problema Sosial di Indonesia. Jakarta: Kencana.Hasan, Sofyan. 1995. Pengantar Hukum Zakat dan Wakaf. Surabaya: AlIkhlas.Hafidhudin, Didin. 1998. PanduanPraktisTentang Zakat, Infaq, Shadaqah. Jakarta: GemaInsani.____________, 2002. Zakat dalam perekonomian modern. Jakarta: Gema Insani. http://www.bps.go.id/ ( di akses tanggal 15 juni 2014 ).Mufraini, arief, 2012. Akuntansi dan manajemen zakat. Mengkomunikasikan Kesadaran dan Mengembangkan Jaringan. Jakarta: Kencana.Muhammad. 2011. Ekonomi Mikro Dalam Perspektif Islam. Yogyakarta : BPFE –Yogyakarta.Pemono, Sjeehul Hadi. 1995. SumberSumber Penggalian Zakat. Jakarta: Pustaka Firdaus.Qardhawi, Yusuf. 1999. Hukum Zakat (Terjemahan), Jakarta: PT Pustaka Litera Antar Nusa.Sugiyono. 2012. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Undang-undang No.23 Tahun 2011 tentang pengelolaan zakat. Kitab Undang-Undang Republik Indonesia.Yin, Robert K. 2009. Studi Kasus, Desain & Metode Ed 1. Jakarta: Rajawali Press.